2023
DOI: 10.1123/iscj.2021-0068
|View full text |Cite
|
Sign up to set email alerts
|

Developing Critical Reflection Skills in a Formal Coach Education Program

Abstract: Alongside knowledge and understanding of the sport (what to coach) and strategies to support learning (how to coach), critical reflection is an important feature of high-quality coaching practice. Accordingly, there is a clear need for evidence-based tools and frameworks for appreciating and developing coaches’ critical reflection skills, through coach education programs. The purpose of this study is to share the results of an intervention intended to develop coaches’ critical reflection skills through a forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…The staff acknowledged this intentional procedure and mentioned its importance in stimulating their professional growth, enriching the teaching-learning process as well. This aligns with previous studies that demonstrated how structured narratives and reflexive conversations are important tools to develop coaches' understanding of their practice (e.g., [46,47]). In this way, the CD also assumes a role as a facilitator of learning [14].…”
Section: Discussionsupporting
confidence: 90%
“…The staff acknowledged this intentional procedure and mentioned its importance in stimulating their professional growth, enriching the teaching-learning process as well. This aligns with previous studies that demonstrated how structured narratives and reflexive conversations are important tools to develop coaches' understanding of their practice (e.g., [46,47]). In this way, the CD also assumes a role as a facilitator of learning [14].…”
Section: Discussionsupporting
confidence: 90%
“…At the end of each year coaches will produce a written reflective account (LO3, LO6, Table 1) describing, explaining, and making sense of a series of critical incidents/moments of surprise. This activity is both informed and framed by the vast body of research literature concerned with practitioner reflection (e.g., Fisher, 2003;Hatton & Smith, 1995;Schön, 2001;Stoszkowski & Collins, 2014a;Vangrunderbeek et al, 2022). Also, at the end of each year, coaches will share a summary of findings from both projects undertaken in that year (LO2, Table 1), with an appropriate audience, to be determined by the coach.…”
Section: Lomentioning
confidence: 99%
“…Nevertheless, examples do exist within the research literature that offer a more optimistic view of how practitioners might become more critically reflective as a result of engaging with wellconsidered professional development programmes. For example, the work of Vangrunderbeek et al (2022) showcases how, in Belgium, gymnastics coaches were able to develop skills for reflection through a well-supported series of learning opportunities over time. Influenced by this, and other cases, within and outside of the field (e.g., Fisher, 2003;Hatton & Smith, 1995), CDIP represents a multi-year opportunity for coaches to undertake inquiry, produce outputs, share those for critical discussion, and be supported to reflect on their processes.…”
Section: Reflective Accountmentioning
confidence: 99%
“…Learner-centered facilitators incorporated questioning and continuous feedback into their pedagogical practice to stimulate reflection, motivate students to learn, and contribute to the development of self-directed learning skills (Carless, 2007;McCombs & Vakili, 2005;Weimer, 2013). Frequent and sustained reflection can result in a more meaningful experience, thus becoming a key process in the education of future coaches who are deeply thoughtful about their professional practice (Kuklick et al, 2015;Milistetd et al, 2017;Vangrunderbeek et al, 2022). Reflection is essential not only in coaches' initial education, but for professional development throughout life (Nash et al, 2018;Trudel et al, 2016).…”
Section: Development Of the E-portfoliomentioning
confidence: 99%